The efficiency of thermosyphon solar water heating system and traditional solar water heating system - et. al., Ridwan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Loop thermosyphon (LT) is typically used for solar water heaters (SHW) to solve the freezing and corrosion issues. The LT – SWH system has a less night time heat loss compared to conventional SWH due to its thermal diode property but a greater heat loss due to the secondary heat exchange. However, the above interactions have rarely had an effect on system performance based on long-term operation [6]. In this paper, the annual results of above two processes, including productive supply day numbers and efficient heat gains and night power losses, was evaluated in this analysis in two separate operating modes on the basis of standard meteorological year data from the City of Fuzhou. Variations of the above variables are addressed with the change in the stated temperature. The results show that the effective delivery days of the LT – SWH system are 139 and 153, respectively, in irregular heating method. The number of days is 168 to 173 in ongoing heating method. The SWH system is predictable to have a higher ratio at nighttime with an annual average of 15.07%, which equates to 6.15% for the LT – SWH system. In fact the LT – SWH method results in a lesser decrease in temperature at night and therefore a smaller raise in the temperature on the following day because of multiple relative heat loss factors running at various hours. The results produced are unpredictable, and lead to an approximately successful heat gain for the same month between November and April. The fixed temperature influences substantially the relative quantities of effective annual supply days and effective annual heat gain, slowly reducing the overall dominance of the LT – SWH method and even changing it as the set temperature increases [12]. This shift is triggered by the biggest daily heat loss leading the domination. In combination with a long static reimbursement time, a conventional SWH system must be substituted by an LT - SWHsystem, particularly when water temperatures are high on demand.